The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/trf.15012
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a transfusion medicine genome wide genotyping array

Abstract: BACKGROUND: Many aspects of transfusion medicine are affected by genetics. Current single-nucleotide polymorphism (SNP) arrays are limited in the number of targets that can be interrogated and cannot detect all variation of interest. We designed a transfusion medicine array (TM-Array) for study of both common and rare transfusion-relevant variations in genetically diverse donor and recipient populations.STUDY DESIGN AND METHODS: The array was designed by conducting extensive bioinformatics mining and consultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…8,12,13 For example, some blood donors can donate repeatedly without hemoglobin deferral, yet others are deferred for low hemoglobin after one or a few donations. Investigating whether there are DNA polymorphism(s) that enable high-intensity donation without low hemoglobin deferral or are associated with pica and RLS will contribute to understanding the physiologic mechanisms of iron absorption and metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,12,13 For example, some blood donors can donate repeatedly without hemoglobin deferral, yet others are deferred for low hemoglobin after one or a few donations. Investigating whether there are DNA polymorphism(s) that enable high-intensity donation without low hemoglobin deferral or are associated with pica and RLS will contribute to understanding the physiologic mechanisms of iron absorption and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Questions about diet were not included because previous studies among donors revealed that dietary differences do not significantly alter iron status in a manner that can be reliably detected by a self-reported dietary history. 12,13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 This cohort was genotyped using a customized Affymetrix Axiom Array with approximately 879,000 single nucleotide polymorphisms (SNPs). 22 Participants were stratified by sex and categorized into six groups that approximated the longitudinal groups ( Figure 1B), differing by selection of females with a previous low hemoglobin deferral, instead of frequent first-time females, who could not be defined because of the crosssectional study design. Groups 1 (2198 females) and 2 (1800 males) consisted of first-time or reactivated donors.…”
Section: Cross-sectional Populationmentioning
confidence: 99%